FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGELOLAAN OBAT MANDIRI DI MASYARAKAT KELURAHAN BELIMBING RT.12 KABUPATEN TABALONG - Fatimatuzahra Fatimatuzahra; Melviani Melviani (Jurnal Farmasi & Sains Indonesia, 2022)
Introduction: Efficient drug management greatly determines the success of the overall management, to avoid inaccurate and irrational calculation of drug requirements so that appropriate drug management is necessary. Drug management aims to ensure the availability of good quality drugs, Purpose : The general purpose of this study was to determine the factors associated with self-administration of drugs in the community in Belimbing Village, rt 12, Murung Pudak District, Tabalong Regency.Method : The method used in this research is using the Cross Sectional method. The sampling technique used in this research is purposive sampling. Data analysis using Spearman Rho test..Results : The results obtained from 70 respondents to self-administration of drugs have a sufficient value (91.4%). There is no relationship between drug management and 3 factors, namely education, income, and information that have a value (p-value > 0.05)Conclusion :Based on the research that has been done, the results show that there is no significant relationship between factors and self-medication management